36 Dietary calcium intake is inadequate in the majority of children with chronic kidney disease. (22nd November 2019) - McAlister, Louise; Silva, Selmy; Shroff, Rukshana
Abstract : Introduction: Adequate calcium (Ca) intake is required for bone mineralisation. KDOQI guidelines for CKD suggest a Ca intake between 100–200% of recommended intakes for healthy children, with an upper limit of 2500 mg/day in older children. We assessed Ca intake from diet, enteral feeds and medications in children with CKD3-5D and healthy controls. Materials and methods: 3-day food diaries were recorded in 23 children with CKD3-5, 23 CKD5D, 27 age-matched controls (median age 9.2 (range 0.8-17.8) years), including doses of phosphate binders and Ca supplements. Dietary Ca was calculated using standardised software. Results: Dietary Ca intake in CKD3-5D was 480 (131-836) vs 724 (218-1507)mg/day in controls (p=0.00002), providing 82% vs 108% (p=0.002) of the Reference Nutrient Intake (RNI) for age (figure 1 ). 74% of children with CKD3-5D received <100% RNI. 26% (12/46) of children with CK3-5D were exclusively enterally fed, achieving 90% RNI. The main Ca sources were dairy products (55% in controls vs 24% in CKD3-5D) and cereals (29% and 21% respectively). 80% (37/46) of CKD children were prescribed Ca-based phosphate binders, 15% Ca supplements and 11% both, increasing median daily Ca intake to 1145 (303-3779)mg/day, 177% RNI. When total daily Ca intake from diet and medications was considered, 7/46 (15%) received <100% RNI, 19 (41%) received >2 x RNI and 3 (6%) exceeded the KDOQI recommended upper limit of 2500 mg Ca/day. Adherence to the prescribed dose of medications was not assessed. 2 (28%) patients with a total Ca intake below the RNI were hypocalcaemic and one patient (5%) having >2 x RNI was hypercalcaemic. Conclusions: In children with CKD3-5D nearly 75% had a dietary Ca below 100% RNI for age. Restriction of dairy products as part of a phosphate controlled diet limits Ca intake. Additional calcium from medications is required in order to meet KDOQI's guideline of 100-200% recommended intakes.